OPERATIONAL ANALYSIS OF PARTIAL LOSS AND THIRD PARTY ON AUTOMOBIL ASSURANCE IN PT. ASKRIDA SYARIAH BRANCH MEDAN - Sari, Sekar; Lubis, Fauzi Arif; Syahriza, Rahmi (Universitas Ibn Khladun Bogor, 2023)
Sharia insurance, especially car insurance, is wide open because the majority of Indonesian people are Muslims and the volume of motor vehicles (Mobiles) is also increasing so rapidly. Besides, the Muslim community has already realised how important it is to be an insurance member. As for the purpose of this research to find out how the management mechanism of partial loss and third party on car insurance in PT. Askrida Insurance Shariah Cab. Field, whether partial loss and third party mechanisms are in line with Islamic financial theory. This research uses inductive qualitative methods with descriptive analysis. This type of research is field research. (field research). This research data includes primary data and secondary data. Research site in PT. Askrida Insurance Shariah Cab. Field, Jl. Sei Batang Assaangan No.43, Babura, Kec, New Field, Medan City, North Sumatra 20222. In data collection using observation methods, interviews, and documentation.. Based on the analysis that the researchers have done, then the results of this study is known that the shariah insurance concerning partial loss and third party on Vehicles in PT. Askrida Insurance Shariah Cab. Fields are in line with Islamic financial theory. Because in the practice of partial loss and third party at PT. Askrida Insurance Shariah Cab. The fields have already used the tabarru's accreditation and the urah's bill, as well as the claims, allocations of funds, and benefits that are in line with the concepts of Islamic financial theory.